Answer:
[tex]\displaystyle p > \frac{1}{4}[/tex].
Step-by-step explanation:
Expand the left-hand side of this equation:
[tex]p\, (x + 1)\, (x - 3) = p\, \left(x^2 - 2\, x - 3\right) = p\, x^2 - 2\, p\, x - 3\, p[/tex].
Collect the terms, so that this quadratic equation is in the form [tex]a\, x^2 + b\, x+ c = 0[/tex]:
[tex]p\, x^2 - 2\, p\, x - 3\, p = x - 4\, p - 2[/tex].
[tex]p\, x^2 - (2\, p + 1)\, x + (p + 2) = 0[/tex].
In this equation:
Calculate the quadratic discriminant of this quadratic equation:
[tex]\begin{aligned}b^2 - 4\, a\, c &= (-(2\, p + 1))^2 - 4\, p\, (p + 2) \\ &= 4\, p^2 + 4\, p + 1 - 4\, p^2- 8\, p = -4\, p + 1\end{aligned}[/tex].
A quadratic equation has no real root if its quadratic discriminant is less then zero. As a result, this quadratic equation will have no real root when [tex]-4\, p + 1 < 0[/tex]. Solve for the range of [tex]p[/tex]:
[tex]\displaystyle p > \frac{1}{4}[/tex].